Meanıng Of Income Based On Fısherman Conscıousness: A Phenomenologıcal Study - Intan Dwi Lestari; Ayudia Sokarina (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to understand in depth the meaning of income based on the awareness of fishermen in Tanjung Luar village, East Lombok Regency. This research uses a qualitative approach with an interpretive paradigm and transcendental phenomenology as methodology.The research results reveal that income based on fishermen's deepest awareness has material and immaterial meaning. Material meaning is interpreted when fishermen feel able to meet their family's needs and set aside their income as future savings. On the other hand, the immaterial meaning is interpreted based on three things, namely (1) pleasure (2) love of work (3) someone has arranged the sustenance, and trust. This research finds a different meaning of income compared to the meaning of income in modern accounting. The meaning of income found in this research can provide awareness in designing more holistic and sustainable programs to improve the overall welfare of fishermen.